APPLICATION OF INTERNATIONAL INTERACTIVE METHODS IN THE VOCATIONAL EDUCATION SYSTEM: ON THE EXAMPLE OF THE EXPERIENCE OF UZBEKISTAN AND KAZAKHSTAN (Multidisciplinary Journal of Science and Technology, 2026)
This article explores the integration of professional education systems between Uzbekistan and Kazakhstan. It analyzes the outcomes of an international master class featuring experts from "APEC PetroTechnic" Higher College (Atyrau) and Aktobe Higher Polytechnic College. The study examines international criteria for assessing education quality in the oil and gas sector and technical fields. Special emphasis is placed on adapting ISO 21001 standards within the framework of Gallaorol Technical School №2.